GPX3 promoter methylation predicts platinum sensitivity in colorectal cancer. Issue 7 (3rd July 2017) - Pelosof, Lorraine; Yerram, Sashidhar; Armstrong, Todd; Chu, Nina; Danilova, Ludmila; Yanagisawa, Breann; Hidalgo, Manuel; Azad, Nilofer; Herman, James G.
ABSTRACT: Epigenetic control of gene expression is a major determinant of tumor phenotype and has been found to influence sensitivity to individual chemotherapeutic agents. Glutathione peroxidase 3 (GPX3, plasma glutathione peroxidase) is a key component of cellular antioxidant regulation and its gene has been reported to be methylated in specific tumor types. GPX3 role in oxidative damage has been associated with sensitivity to platinums in other tumors but its importance in colorectal cancer (CRC) has not been determined. We examined the role of GPX3 methylation in colorectal carcinoma in determining sensitivity to platinum drugs using primary tumor specimens, cell lines, knockdown cell lines, and tumor cell line xenografts. We find GPX3 promoter region methylation in approximately one third of CRC samples and GPX3 methylation leads to reduced GPX3 expression and increased oxaliplatin and cisplatin sensitivity. In contrast, in cell lines with high baseline levels of GPX3 expression or with the ability to increase GPX3 expression, platinum resistance is increased. The cisplatin IC50 in GPX3- methylated cell lines is approximately 6-fold lower than that in GPX3 -unmethylated lines. Additionally, knockdown cell lines with essentially no GPX3 expression require N-acetylcysteine to survive in culture underscoring the importance of GPX3 in redox biology. In vivo, GPX3 methylation predicts tumor xenograft sensitivity to platinum with regression of GPX3 knockdown xenografts with platinum treatment but continued growth of GPX3 wild type xenografts in the presence of platinum. These studies demonstrate the importance of GPX3 for CRC cells resistance to platinums and the potential utility of GPX3 methylation status as a predictive biomarker for platinum sensitivity in CRC.